IDENTIFIKASI PENYEBAB PENDING KLAIM PADA BANGSAL PENYAKIT DALAM DI RSUD DR. RASIDIN PADANG - Yulia, Yulfa; Desnita Tasri, Yanti; Marcelo Putra, Dito (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Pending claims are a common obstacle ini the process of submitting claims to BPJS Kesehatan, potentially causing financial and administrative delays for hospitals and affecting the timely distribution of medical and non-medical service fees. This study aims to identify the causes of pending claims in the internal medicine ward at RSUD dr. Rasidin Padang. The research i a descriptive quantitative study using an observational approach. The population consisted of 60 pending claims file, with a sample of 38 files. The result showed that most causes of pending claims were due to inaccurate diagnostic coding(71.1%), inappropriate medical treatment procedures(26.3%), and incomplete supporting document attachments(31.6%). The study concludes that inaccurate diagnosis codes, inappropriate medical procedures, and incomplete examination attachments are the main factors contributing to pending claims in the internal medicine ward of RSUD dr. Rasidin Padang. Therefore, it is recommended that the hospital conduct regular monitoring and provide periodic training for coding officers to minimaze the risk of claim delays. Keywords: Pending Claims, Diagnosis Coding,, Supporting Documents, Medical Record